Versatility of Chitosan-Based Biomaterials and Their Use as Scaffolds for Tissue Regeneration - José Carlos Viana Ribeiro; Rodrigo Silveira Vieira; Iracema Matos Melo; Vilana Maria Adriano Araújo; Vilma Lima (The Scientific World Journal)
Chitosan is a naturally occurring polysaccharide obtained from chitin, present in abundance in the exoskeletons of crustaceans and insects. It has aroused great interest as a biomaterial for tissue engineering on account of its biocompatibility and biodegradation and its affinity for biomolecules. A significant number of research groups have investigated the application of chitosan as scaffolds for tissue regeneration. However, there is a wide variability in terms of physicochemical characteristics of chitosan used in some studies and its combinations with other biomaterials, making it difficult to compare results and standardize its properties. The current systematic review of literature on the use of chitosan for tissue regeneration consisted of a study of 478 articles in the PubMed database, which resulted, after applying inclusion criteria, in the selection of 61 catalogued, critically analysed works. The results demonstrated the effectiveness of chitosan-based biomaterials in 93.4% of the studies reviewed, whether or not combined with cells and growth factors, in the regeneration of various types of tissues in animals. However, the absence of clinical studies in humans, the inadequate experimental designs, and the lack of information concerning chitosan’s characteristics limit the reproducibility and relevance of studies and the clinical applicability of chitosan.